Convergent approach to persistent atrial fibrillation ablation: long-term single-centre safety and efficacy - Carpenter, Alexander; Pannell, Laura M. K.; Rizvi, Syed I. A.; Maciver, Kirsty; Rajakaruna, Cha; Ciulli, Franco; Duncan, Edward R.; Thomas, Glyn; Barman, Palash; Bond, Richard; Nisbet, Ashley M. (Frontiers in Cardiovascular Medicine, 2024)
Background: Efforts to maintain sinus rhythm in patients with persistent atrial fibrillation (PsAF) remain challenging, with sub-optimal long-term outcomes.Methods: All patients undergoing convergent PsAF ablation at our centre were retrospectively analysed. The Atricure Epi-Sense® system was used to deliver LA posterior wall radiofrequency ablation surgically, with follow-on endocardial ablation.Results: 24 patients underwent convergent PsAF ablation. 21 (84%) were male with a median age of 63. 12 (50%) were obese. 71% had a severely dilated left atrium and the majority (63%) had preserved left ventricular function. All were longstanding persistent. 18 (75%) had AF duration >2 years.There were no endocardial procedure complications. At 36 months all patients were alive with no new stroke / TIA. Freedom from documented AF at 3, 6,12,18, 24 and 36 months was 83%, 78%, 74%, 74%, 74% and 61%, respectively. There were no major surgical complications, with 5 minor complications recorded comprising minor wound infection, pericarditic pain and hernia.